Prophetic Leadership in Islamic Schools: Transforming Teacher Performance and Student Achievement - Anggraeni, Anggraeni; Muhaemin, Muhaemin; Sulistiani, Ino (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2025)
Prophetic leadership, rooted in the values of humanization, liberation, and transcendence, has gained attention as an ethical and values-based leadership model in Islamic education. This study examines the influence of prophetic leadership on teacher performance and student achievement at Madrasah Ibtidaiyah Datok Sulaiman Palopo. Using a quantitative correlational design, the study collected data from teachers and students using structured questionnaires and academic performance records. The data were analyzed using multiple regression and Pearson correlation tests to determine the relationship between prophetic leadership, teacher performance, and student achievement. The findings indicate that teachers perceive the principal’s leadership as highly aligned with prophetic values, particularly in fostering ethical guidance, professional motivation, and collaborative engagement. A significant positive correlation was found between prophetic leadership and teacher performance, suggesting that teachers who experience strong moral and professional support from school leaders demonstrate higher instructional effectiveness and classroom engagement. Additionally, student achievement was significantly influenced by the leadership approach, reinforcing the idea that values-driven leadership fosters a positive learning environment. The study highlights the need for Islamic schools to integrate participatory leadership practices, ensuring teachers have greater autonomy in decision-making. It also emphasizes expanding leadership strategies beyond teacher development to engage students and parents actively. Future research should explore how prophetic leadership can adapt to contemporary educational challenges, ensuring its continued relevance in enhancing teacher effectiveness and student success.